Identification of Anti-Long Chain Saturated Fatty Acid IgG Antibodies in Serum of Patients with Type 2 Diabetes - Dequina A. Nicholas; Lorena M. Salto; Ava M. Boston; Nan Sun Kim; Marco Larios; W. Lawrence Beeson; Anthony F. Firek; Carlos A. Casiano; William H. R. Langridge; Zaida Cordero-MacIntyre; Marino De Leon (Mediators of Inflammation, 2015)
High levels of serum long chain saturated fatty acids (LCSFAs) have been associated with inflammation in type 2 diabetes. Dietary SFAs can promote inflammation, the secretion of IgG antibodies, and secretion of the proinflammatory cytokine IL-1β. This study characterizes anti-LCSFA IgG antibodies from patients with type 2 diabetes. Serum samples from several cohorts with type 2 diabetes were analyzed for the presence of anti-LCSFA IgG, the cytokine IL-1β, and nonesterified fatty acids. Anti-LCSFA IgG was isolated from patient samples and used for in vitro characterization of avidity and specificity. A cohort participating in En Balance, a diabetes health education program that improved diabetes management, tested positive for anti-LCSFA IgG. Following the 3-month program, the cohort showed a significant reduction in anti-LCSFA IgG levels. Anti-LCSFA antibodies isolated from these patients demonstrated high avidity, were specific for long chain SFAs, and correlated with serum fatty acids in patients with managed type 2 diabetes. Interestingly, anti-LCSFA IgG neutralized PA-induced IL-1β secretion by dendritic cells. Our data shows that nonesterified SFAs are recognized by IgG antibodies present in human blood. The identification of anti-LCSFA IgG antibodies in human sera establishes a basis for further exploration of lipid induced immune responses in diabetic patients.